System for notational analysis in small-sided soccer games - van Maarseveen, M. J. J.; Oudejans, R. R. D.; Savelsbergh, G. J. P. (International Journal of Sports Science & Coaching, 2017)
The objective of this study was to compose an objective and detailed notational analysis system for 3 vs. 2 + GK small-sided soccer games, in which three roles are examined: attacker with ball, attacker without ball and defender. The actions and the outcome of the actions were registered for each player and in each role. Players earn points for each action and outcome according to an a priori determined scheme. Performance scores for each role are calculated as the average number of points a participant earns per trial. This notation system was tested on 19 highly talented female soccer players and validity and reliability of the system were determined. In addition, practical applications were discussed and the most important items of the notation system were determined and using only these items, a simplified notation system was proposed. The notation system has high ecological validity and can discriminate the high and low categorized players, but further development is necessary to increase the reliability of the system. FROM AUTHOR